The Effect of Topping and spacing on the production and seeds quality of Cucumber (Cucumis sativus L.) - Rahmat Ali Saban; Suwardi Suwardi; Andika Nurul Huda (SINTA Journal (Science, Technology, and Agricultural), 2022)
This research is intended to obtain information on the yield power of these hybrid candidates. This research was conducted in November 2020 – January 2021. Located on the land of PT. Aditya Sentana Agro, Jl. Zentana No. 87, Karangploso District, Malang Regency, East Java. This study used a Randomized Block Design (RCBD) with 1 treatment factor, namely 5 different genotypes consisting of 4 F1 melon lines and 1 comparison variety, namely Melindo-15 F1. 5 genotype, namely M0 : Melindo-15 F1, M1 : 821-41 x 1197- 118, M2 : 1197-19 x 1211-32, M3 : 1197-127 x 821-70, and M4 : 1211-7 x 1197-106. The results showed that the data information of the melon F1 line as a candidate variety with superior characters was significantly different on the parameters of harvest age and not significantly different on all parameters in quantitative research, weight of 1000 grains, weight per fruit, production per Ha. The results of the selection of 4 F1 melon lines that have yield potential exceeding the Melindo-15 F1 variety, namely the type of melon M1 (821-41 x 1197-118) with production per ha of 25.24 tons/ha and M3 (1197-127 x 821- 70) with production per Ha of 21.69 Ton/Ha